2020
DOI: 10.3892/ol.2020.11701
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of B7‑H4 promotes renal cell carcinoma progression by recruiting tumor‑associated neutrophils via upregulation of CXCL8

Abstract: The immune checkpoint molecule B7 family member H4 (B7-H4) plays a similar role to programmed death-ligand 1 in tumor immune evasion by regulating T-cell-mediated immune responses. However, besides the role in T-cell immunity, B7-H4 also affects tumor cell biology by promoting tumor cell proliferation, metastasis and angiogenesis. In order to explore the effect of B7-H4 on tumor cell biology, it is necessary to investigate the gene expression profile when B7-H4 is overexpressed. In the present study, 786-O cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…The bulk of the researchers have reported the mechanism of the mutual effect between VTCN1 and infiltrating immune cells leading to tumorigenesis. Overexpression of VTCN1 accelerates renal cell carcinoma advancement by recruitment of tumorrelated neutrophils up-regulating the CXCL8 in the report by Li et al [33] . Others included cervical cancer [34] , thymic epithelialtumor [24] , epithelial ovarian cancer [35] , metastatic colorectal cancer [28] , and non-small cell lung cancer [36] , where the connection between VTCN1 and immune cells was explained severally.…”
Section: Experimental Verificationmentioning
confidence: 90%
“…The bulk of the researchers have reported the mechanism of the mutual effect between VTCN1 and infiltrating immune cells leading to tumorigenesis. Overexpression of VTCN1 accelerates renal cell carcinoma advancement by recruitment of tumorrelated neutrophils up-regulating the CXCL8 in the report by Li et al [33] . Others included cervical cancer [34] , thymic epithelialtumor [24] , epithelial ovarian cancer [35] , metastatic colorectal cancer [28] , and non-small cell lung cancer [36] , where the connection between VTCN1 and immune cells was explained severally.…”
Section: Experimental Verificationmentioning
confidence: 90%
“…120 Recent studies indicated the broad spectrum of patients' tumors that have been associated with aberrant B7-H4 expression across a wide variety of cancers, including colorectal, craniopharyngioma, RCC, BC, prostate cancer, pancreatic cancer, esophageal squamous cell carcinoma (ESCC), and cervical cancer. [137][138][139][140][141][142][143][144] Furthermore, serum sB7-H4 may be a valuable prognostic marker in patients in this wide spectrum of cancers. In patients with non-metastatic ccRCC, the high levels of sB7-H4 along with elevated PB neutrophil count were associated with either poor progression-free survival (PFS) or OS.…”
Section: New B7 Family Checkpoints Moleculesmentioning
confidence: 99%
“…The chemokine CXCL8 and the chemokine receptor CXCR4 are also involved in the recruitment of neutrophils in the tumor microenvironment. Inhibiting CXCL8 or blocking CXCR4 can inhibit the infiltration of TANs in TME ( 304 307 ). IL-6 can also attract TANs to the tumor environment and can attenuate and reverse the pro-inflammatory effects of neutrophils in the tumor microenvironment thus leading to immune-killing resistance.…”
Section: Tans-targeted Therapymentioning
confidence: 99%